Inhibition or knockdown of ABC transporters enhances susceptibility of adult and juvenile schistosomes to Praziquantel. - Ravi S Kasinathan; Lalit Kumar Sharma; Charles Cunningham; Thomas R Webb; Robert M Greenberg (Public Library of Science (PLoS), 2014)
Parasitic flatworms of the genus Schistosoma cause schistosomiasis, a neglected tropical disease that affects hundreds of millions. Treatment of schistosomiasis depends almost entirely on the drug praziquantel (PZQ). Though essential to treating and controlling schistosomiasis, a major limitation of PZQ is that it is not active against immature mammalian-stage schistosomes. Furthermore, there are reports of field isolates with heritable reductions in PZQ susceptibility, and researchers have selected for PZQ-resistant schistosomes in the laboratory. P-glycoprotein (Pgp; ABCB1) and other ATP binding cassette (ABC) transporters remove a wide variety of toxins and xenobiotics from cells, and have been implicated in multidrug resistance (MDR). Changes in ABC transporter structure or expression levels are also associated with reduced drug susceptibility in parasitic helminths, including schistosomes. Here, we show that the activity of PZQ against schistosome adults and juveniles ex vivo is potentiated by co-administration of either the highly potent Pgp inhibitor tariquidar or combinations of inhibitors targeting multiple ABC multidrug transporters. Adult worms exposed to sublethal PZQ concentrations remain active, but co-administration of ABC transporter inhibitors results in complete loss of motility and disruption of the tegument. Notably, juvenile schistosomes (3-4 weeks post infection), normally refractory to 2 µM PZQ, become paralyzed when transporter inhibitors are added in combination with the PZQ. Experiments using the fluorescent PZQ derivative (R)-PZQ-BODIPY are consistent with the transporter inhibitors increasing effective intraworm concentrations of PZQ. Adult worms in which expression of ABC transporters has been suppressed by RNA interference show increased responsiveness to PZQ and increased retention of (R)-PZQ-BODIPY consistent with an important role for these proteins in setting levels of PZQ susceptibility. These results indicate that parasite ABC multidrug transporters might serve as important targets for enhancing the action of PZQ. They also suggest a potentially novel and readily-available strategy for overcoming reduced PZQ susceptibility of schistosomes.